Heart Cells with Regenerative Potential from Pediatric Patients with End Stage Heart Failure: A Translatable Method to Enrich and Propagate. (14th August 2012) - Steele, Ann; Boucek, Robert J.; Jacobs, Jeffrey Phillip; Steele, Peter; Asante-Korang, Alfred; Chamizo, Wilfredo; Steele, Jasmine; Chai, Paul J.; Quintessenza, James A.
Abstract : Background . Human cardiac-derived progenitor cells (hCPCs) have shown promise in treating heart failure (HF) in adults. The purpose of this study was to describe derivation of hCPCs from pediatric patients with end-stage HF. Methods . At surgery, discarded right atrial tissues (hAA) were obtained from HF patients (n = 25 ; hAA-CHF). Minced tissues were suspended in complete (serum-containing) DMEM. Cells were selected for their tissue migration and expression of stem cell factor receptor (hc-kit). Characterization of hc-kit positive cells included immunohistochemical screening with a panel of monoclonal antibodies. Results . Cells, including phase-bright cells identified as hc-kit positive, spontaneously emigrated from hAA-CHF in suspended explant cultures (SEC) after Day 7. When cocultured with tissue, emigrated hc-kit positive cells proliferated, first as loosely attached clones and later as multicellular clusters. At Day 21 5% of cells were hc-kit positive . Between Days 14 and 28 hc-kit positive cells exhibited mesodermal commitment (GATA-4 positive and NKX2 .5 positive ); then after Day 28 cardiac lineages (flk-1 positive, smooth muscle actin positive, troponin-I positive, and myosin light chain positive ). Conclusions . C-kit positive hCPCs can be derived from atrial tissue of pediatric patients with end-stage HF. SEC is a novel culture method for derivation of migratory hc-kit positive cells that favors clinical translation by reducing the need for exogenously added factors to expand hCPCs in vitro .